MANUSIA SEBAGAI CO-CREATOR ALLAH: Sebuah Refleksi Etis-Teologis atas Kerja menurut Paham Ensiklik Laborem Exercens - Moa, Antonius (UNIKA Santo Thomas, 2008)
Work is a human activity. As an activity, this work is closely related to human being as the worker. For human being, work, as a transitive activity, is not only as an activity to change the nature, to adjust with his need, but to strengthen and to develop human dignity as image of God, as a cocreator with God.